THE ADVANTAGE OF THE ALL-ON-SIX AND ALL-ON-EIGHT TECHNIQUE COMPARED TO THE ALL-ON-FOUR TECHNIQUE - Marius Constantin Moraru; Catalin Mihai Buzduga; Irina Luciana Gurzu; Vasile-Deniss Mereuta; Oana Elena Ciurcanu; Mihail Balan; Edlibi Al Hage Walid; Laura Iulia Bozomitu; Alin-Horatiu Nedelcu; Mihaela Mitrea (Romanian Society of Oral Rehabilitation, 2024)
Edentulism is a prevalent oral health issue that has a detrimental social and psychological impact on patients 'quality of life. The treatment option adopted has a significant impact on the level of quality with the goal can be achieved. For edentulous patients, implant-supported fixed restorations are a well-established treatment modality. Implant dentistry philosophies and procedures have evolved and changed over the time to give esthetics and functional outcomes. Immediate loading has various advantages over traditional loading without sacrificing the quality of the output. An immediate fixed provisional promotes a high level of patient satisfaction with respect to esthetics, phonetics, mastication and psychological comfort, enabling patients to return to their normal routine and maintain quality of life within a short period of time. Without question, the optimal solution for any edentulous patient from whom it is still clinically viable to place implants is all-on-X dental implant solution. Whether All-on-four All-on-five, All-on-six or any variation of a full implant supported design, there is a best option for quality of life, long term durability, bone maintenance, health improvement and frankly happiness.